Pengelolaan Lingkungan dan Infrastruktur Berkelanjutan di Kawasan Pariwisata Pesisir: Staudi Kasus Munggu, Badung - Irawan, I Wayan Putra; Jaya, Kadek Merta; Kurniawan, Agus (Riviera Publishing, 2025)
Coastal tourism areas face unique challenges in balancing economic growth with environmental conservation and the provision of adequate infrastructure. This study aims to analyze environmental management practices and sustainable infrastructure development in Munggu, Badung, as one of the rapidly developing coastal areas in Bali. Using a qualitative and quantitative approach, this research explores the perceptions of local communities, tourism stakeholders, and the government regarding the impact of tourism on the environment and the effectiveness of existing management policies. The findings are expected to provide strategic recommendations for more sustainable coastal tourism development, particularly in Munggu, and serve as a model for similar areas in Indonesia.